High‐resolution definition of humoral immune response correlates of effective immunity against HIV. Issue 3 (26th March 2018) - Alter, Galit; Dowell, Karen G; Brown, Eric P; Suscovich, Todd J; Mikhailova, Anastassia; Mahan, Alison E; Walker, Bruce D; Nimmerjahn, Falk; Bailey‐Kellogg, Chris; Ackerman, Margaret E
Abstract: Defining correlates of immunity by comprehensively interrogating the extensive biological diversity in naturally or experimentally protected subjects may provide insights critical for guiding the development of effective vaccines and antibody‐based therapies. We report advances in a humoral immunoprofiling approach and its application to elucidate hallmarks of effective HIV‐1 viral control. Systematic serological analysis for a cohort of HIV‐infected subjects with varying viral control was conducted using both a high‐resolution, high‐throughput biophysical antibody profiling approach, providing unbiased dissection of the humoral response, along with functional antibody assays, characterizing antibody‐directed effector functions such as complement fixation and phagocytosis that are central to protective immunity. Profiles of subjects with varying viral control were computationally analyzed and modeled in order to deconvolute relationships among IgG Fab properties, Fc characteristics, and effector functions and to identify humoral correlates of potent antiviral antibody‐directed effector activity and effective viral suppression. The resulting models reveal multifaceted and coordinated contributions of polyclonal antibodies to diverse antiviral responses, and suggest key biophysical features predictive of viral control. Synopsis: Interrogation and systematic analysis of the humoral immune response define correlates of antibody effector function and humoral responses associated with spontaneous HIV‐1 suppression, indicating new metrics, which may be relevant for HIV vaccine trials. High resolution profiling of antibody features and effector functions is used to evaluate immune responses in HIV infection. Humoral responses associated with spontaneous viral suppression are modeled. Features of antibodies associated with potent effector function are defined. The identified antibody markers of HIV viral suppression and potent effector function may be useful for benchmarking HIV vaccines. Abstract : Interrogation and systematic analysis of the humoral immune response define correlates of antibody effector function and humoral responses associated with spontaneous HIV‐1 suppression, indicating new metrics, which may be relevant for HIV vaccine trials.